Mental health and adaptive functioning among school-aged children living with HIV in Zambia - Kalungwana, Lisa; Malcolm-Smith, Susan; Schrieff, Leigh (Frontiers in Psychiatry, 2022)
Background: The number of children living with HIV (CLWHIV) has been increasing, reflected by lower mortality. However, this change is coupled with higher rates of morbidity, where CLWHIV face considerable challenges, including neurocognitive delays and mental health and behavioral functioning challenges. Despite Sub-Sahara accounting for the highest number of CLWHIV, there is still limited research on the effects of HIV on child mental health and adaptive functioning. Method: Mental health and adapting functioning were assessed in 120 children. The sample included 62 CLWHIV and 58 demographically-matched HIV-uninfected children aged 6 -12 years. Mental health was assessed using the Connors, while adaptive functioning was assessed using the Vineland Adaptive Behavioural Scale (VABS). Results: Scores obtained were within average ranges for mental health (T-score 40-59) and adaptive functioning standard scores (70-115). However, CLWHIV had significantly higher mental health problems than uninfected children in executive functioning and aggressiveness (p<.05). CLWHIV had lower adaptive functioning scores on the VABS Communication domain although these differences were not significant. In the Daily Living Skills domain, CLWHIV had significantly higher scores than the HIV-uninfected children (p<.05) There were no significant differences in the Socialization subdomain. Furthermore, CLWHIV had significantly higher scores on the Maladaptive Behavior scales of the VABS’ internalizing and externalizing subdomains. Conclusion: Challenges to mental health and adaptive functioning are still pervasive among CLWHIV. These findings support the need to develop support mechanisms for CLWHIV to help address mental health and adaptive functioning problems, especially as they progress into adolescence.